2006 IEEE International Conference on Systems, Man and Cybernetics 2006
DOI: 10.1109/icsmc.2006.385119
|View full text |Cite
|
Sign up to set email alerts
|

Study on Motion Forms of Mobile Robots Generated by Q-Learning Process Based on Reward Databases

Abstract: This paper investigates the motion forms of robots generated by the Q-Learning algorithm during the learning process. We analyzed the manner in which a caterpillar robot, which performs looping motions using two actuators, acquires advance actions by focusing on the process. By observing a series of processes, we confirmed that various motion forms appeared or disappeared as a result of their interactions with the learning process and approach an optimum motion form. In most algorithms, such motion forms canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In addition, the discount factor significantly affected the form of this maximum reward group. In [15] and [16], we stated that it is easy to produce the final motion form with very few motion patterns when the discount factor, , is set to a large value. In contrast, an inverse effect was confirmed when was set to a smaller value.…”
Section: B Emergence Of Motion Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the discount factor significantly affected the form of this maximum reward group. In [15] and [16], we stated that it is easy to produce the final motion form with very few motion patterns when the discount factor, , is set to a large value. In contrast, an inverse effect was confirmed when was set to a smaller value.…”
Section: B Emergence Of Motion Formsmentioning
confidence: 99%
“…In our previous work, we studied the forward motion of a caterpillar robot using Q-learning, which is a typical and simple method of reinforcement learning [15], [16]. The results showed that reinforcement learning enabled the robot to achieve an unexpected motion pattern and exhibit good performance for a given task.…”
Section: Introductionmentioning
confidence: 97%
“…Littman and Michael et al [22] used Q-learning algorithm to realize autonomous movement control of robots. Hara et al [23] used machine learning control algorithms to control robots and improve learning efficiency.…”
Section: Introductionmentioning
confidence: 99%